A Linguistic Analysis of Tennis Players’ Speeches - Rezqallah, May Stephan; Jasim, Riham Khalid (Al-Adab Journal, 2020)
This study is under the title "A Linguistic Analysis of Tennis Players’ Speeches", which tackles the English speeches that are delivered by tennis players (native and non-native speakers) in the championship’s final game. The problem lies in encoding and decoding the native and non-native tennis players’ speeches being unplanned, and they are delivered in a formal setting which is a rare case. In other words, in perceiving these speeches, there are many speech sounds that distract the native English listeners’ ears like pronouncing the word Zurich as /θurik/; whereas the BBC pronunciation is [ˈzjʊərɪʔk]. The study aims at detecting phonologically the differences between the English accent of the tennis players (native and non-native speakers) and BBC as well as showing how this causes a problem in the process of encoding and decoding.